Understanding the Political-Economic Impacts on Inception and Operational Effectiveness of an Audit Oversight Body: Case of an Emerging Economy - Md. Atiqur Rahman; Salah Uddin Rajib; Mahfuzul Hoque (The Indonesian Journal of Accounting Research, 2023)
This paper aims to analyze the impacts of the political-economic setup of an emerging economy on audit oversight arrangements introduced due to isomorphic pressure. We adopted a mixture of qualitative research methods for the study. Expert interviews and document analyses were conducted. Structuration theory and, more specifically, the institutional relational dynamics framework proposed by Dillard et al. (2004) have been utilized to understand the phenomenon theoretically. We found that the Financial Reporting Council (FRC) was established in Bangladesh in 2016 within the context attributed to relatively ineffective corporate governance in the face of international and local stakeholder pressures. Financial policymakers responded strategically to the coercive pressure from donor agencies. Deviating from global practice, the majority of government nominees instead of experts have been ensured in FRC. Moreover, instead of reactivating six existing financial regulators, the government buffered the creation of FRC for a decade. Low resources have been endowed, limiting the capacity of FRC to bring about structural changes. In line with the field-level norm, the body has already become dormant and susceptible to politicization. There are few studies on audit oversight arrangements in the least Developed Countries (LDCs). Our paper addresses a unique political-economic setup influencing the effectiveness of oversight bodies. Structuration theory assists us in magnifying the scenario further. The study can determine the actual trajectory of enhancing audit quality through the audit oversight body in LDCs. However, instead of generalizing the finding, this study can be considered a case study as LDCs are unique in various characteristics.